2011
DOI: 10.1523/jneurosci.3100-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Entorhinal Cortex Promotes Adult Neurogenesis and Facilitates Spatial Memory

Abstract: Deep brain stimulation (DBS)is an established therapeutic modality for the treatment of movement disorders and an emerging therapeutic approach for the treatment of disorders of mood and thought. For example, recently we have shown that DBS of the fornix may ameliorate cognitive decline associated with dementia. However, like other applications of DBS, the mechanisms mediating these clinical effects are unknown. As DBS modulates neurophysiological activity in targeted brain regions, DBS might influence cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
285
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(301 citation statements)
references
References 66 publications
13
285
1
2
Order By: Relevance
“…Lowering corticosterone secretion from midlife (Montaron et al 2006) or a midlife vitamin A supplementation (Touyarot et al 2013) for the rest of the animal's life prevents age-related spatial memory deficits and age-related decline in neurogenesis. In a young subject, pharmacological approaches, consisting of peripheral treatment with the cognitive enhancer ginseng (Qiao et al 2005), the peptidergic drug P21 (Li et al 2010), the histone acetyltransferases CBP/p300 (Chatterjee et al 2013), hippocampal gene transfer of VEGF (Cao et al 2004), blockade of NR2B-containing NMDAR (Hu et al 2008), stimulation of entorhinal cortex (Stone et al 2011a), or deletion of Toll-like receptors (TLRs) (Okun et al 2010), all promoted adult neurogenesis and facilitated memory performances in different learning tasks (contextual fear-conditioning paradigm, associative passive avoidance, and water maze).…”
Section: Correlationsmentioning
confidence: 99%
“…Lowering corticosterone secretion from midlife (Montaron et al 2006) or a midlife vitamin A supplementation (Touyarot et al 2013) for the rest of the animal's life prevents age-related spatial memory deficits and age-related decline in neurogenesis. In a young subject, pharmacological approaches, consisting of peripheral treatment with the cognitive enhancer ginseng (Qiao et al 2005), the peptidergic drug P21 (Li et al 2010), the histone acetyltransferases CBP/p300 (Chatterjee et al 2013), hippocampal gene transfer of VEGF (Cao et al 2004), blockade of NR2B-containing NMDAR (Hu et al 2008), stimulation of entorhinal cortex (Stone et al 2011a), or deletion of Toll-like receptors (TLRs) (Okun et al 2010), all promoted adult neurogenesis and facilitated memory performances in different learning tasks (contextual fear-conditioning paradigm, associative passive avoidance, and water maze).…”
Section: Correlationsmentioning
confidence: 99%
“…In Study 1, 5-bromo-2′deoxyuridine (BrdU; Sigma) was injected on post-stimulation day 3 (50 mg/kg every 6 h for 24 h) and animals were sacrificed the next day, as previously described (Encinas et al, 2011;Hamani et al, 2011;Stone et al, 2011;Toda et al, 2008). In Study 2, BrdU was given from post-stimulation days 3-5 (50 mg/kg every 6 h) and animals were sacrificed 28 days later.…”
Section: Methodsmentioning
confidence: 99%
“…In rodents, DBS increases levels of hippocampal serotonin (Adachi et al, 2005;Hamani et al, 2010b) and brain derived neurotrophic factor (Gersner et al, 2010;. In a recent series of studies, stimulation of limbic structures (Encinas et al, 2011;Hamani et al, 2011;Stone et al, 2011;Toda et al, 2008) or the Acb (Schmuckermair et al, 2013) has been shown to increase hippocampal neurogenesis. As the vmPFC has direct and indirect connections with the hippocampus (Vertes, 2004(Vertes, , 2006, it is conceivable to hypothesize that treatments that modulate its activity (e.g.…”
Section: Deep Brain Stimulation (Dbs) Is Currently Being Investigatedmentioning
confidence: 99%
“…Application of acute high-frequency DBS in hippocampus EC of mice could lead to a transiently promoted proliferation in the dentate gyrus (DG) [142], and these DBS-induced neurons merged with hippocampal circuits once they were mature.…”
Section: Hippocampus Enthorinal Cortex (Ec)mentioning
confidence: 99%